2022
DOI: 10.1007/s00122-022-04191-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping, transcriptomic sequencing and metabolic profiling indicated a glutathione S-transferase is responsible for the red-spot-petals in Gossypium arboreum

Abstract: Colored petal spots are correlated with insect pollination e ciency in Gossypium species. However, molecular mechanisms concerning the formation of red spots on Gossypium arboreum owers remain elusive. In the current study, the Shixiya1-R (SxyR, with red spots) × Shixiya1-W (SxyW, without red spots) segregating population was utilized to determine that the red-spot-petal phenotype was levered by a single dominant locus. This phenotype was expectedly related to the anthocyanin metabolites, wherein the cyanidin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Our genetic analysis revealed that the red petals of LR were controlled by a single dominant gene GhTT19 LR . A recent study reported that Gar07G08900 , a GST homologue gene, is responsible for the red‐spot petals in G. arboreum (Zhang et al ., 2022 ). An R2R3‐MYB113 could control base spot formation in Gossypium barbadense (Abid et al ., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our genetic analysis revealed that the red petals of LR were controlled by a single dominant gene GhTT19 LR . A recent study reported that Gar07G08900 , a GST homologue gene, is responsible for the red‐spot petals in G. arboreum (Zhang et al ., 2022 ). An R2R3‐MYB113 could control base spot formation in Gossypium barbadense (Abid et al ., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reverse genetic and molecular studies indicated that cotton GST was an essential gene for anthocyanin accumulation in the red leaf of upland cotton (Li et al ., 2020 ; Shao et al ., 2021 ). Also, Gar07G08900 , a GST homologue was responsible for the red‐spot‐petals in Gossypium arboreum (Zhang et al ., 2022 ). However, no forward genetic and genomic study was reported for more details about anthocyanin pigmentation in cotton petals.…”
Section: Introductionmentioning
confidence: 99%